2018
DOI: 10.1186/s12931-018-0896-7
|View full text |Cite
|
Sign up to set email alerts
|

Significant predictors of medically diagnosed chronic obstructive pulmonary disease in patients with preserved ratio impaired spirometry: a 3-year cohort study

Abstract: BackgroundPreserved ratio impaired spirometry (PRISm) is an incompletely understood respiratory condition. We investigated the incidence and significant predictive factors of chronic obstructive pulmonary disease (COPD) in PRISm patients.MethodsFrom 11,922 subjects registered in the Korea National Health and Nutrition Examination Survey, never or light smokers, young subjects, and those already medically diagnosed with COPD (defined by ICD-10 code and prescribed medication) were excluded. The 2666 remaining su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 34 publications
(37 reference statements)
5
36
2
Order By: Relevance
“…Kim et al reported that COPD was found in approximately 23% of the participants aged 40 years or over with more than 10 pack-year smoking history (17). This finding was consistent with the findings by Hwang et al (15) forced expiratory volume in 1 second (FEV1)/forced vital capacity (FVC) >0.7 with reduced FEV1 <80% predicted], they are most likely to develop COPD (18,19). Both raising awareness of COPD and increasing PFTs are important and necessary to manage and prevent the disease in the highrisk population.…”
Section: Copd Awarenesssupporting
confidence: 73%
“…Kim et al reported that COPD was found in approximately 23% of the participants aged 40 years or over with more than 10 pack-year smoking history (17). This finding was consistent with the findings by Hwang et al (15) forced expiratory volume in 1 second (FEV1)/forced vital capacity (FVC) >0.7 with reduced FEV1 <80% predicted], they are most likely to develop COPD (18,19). Both raising awareness of COPD and increasing PFTs are important and necessary to manage and prevent the disease in the highrisk population.…”
Section: Copd Awarenesssupporting
confidence: 73%
“…COPD is highly prevalent and a major cause of death worldwide 24 . However, only a small number (2-3%) of patients with COPD are diagnosed to have this condition by doctors in clinics in Korea 25 , as shown in world-wide 26 . COPD needs sustained follow-up, so primary care has a significant role in its management.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with preserved ratio impaired spirometry (PRISm), previously called restrictive pulmonary function [1,2], Global Initiative for Chronic Obstructive Lung Disease (GOLD)-unclassified [3] or the nonspecific pattern [4,5], do not meet the criteria for chronic obstructive pulmonary disease (COPD) but exhibit increased respiratory symptoms [1,2,6], increased cardiovascular comorbidity [7][8][9][10][11][12][13][14][15] and increased mortality [6,7,[16][17][18][19]. This neglected subgroup has often been excluded in research papers, though the existing studies to date estimate the prevalence of PRISm to range between 3.0% and 20% in adults [3,5,7,[18][19][20][21][22][23]. Few of these studies were conducted in the general population and they rarely performed repeated spirometry measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies of subjects with PRISm are scarce and have mostly been conducted in populations of current or past smokers. Some have suggested PRISm is a fluctuating state, serving as an intermediate phase between normal spirometry and COPD for a subset of individuals [2,3,5,18,20]. Others have identified risk factors for PRISm, which include female sex [3,18], smoking, advanced age, metabolic syndrome [24,25], a history of tuberculosis [26], systemic inflammation [4,[27][28][29], exposure to fine dust [30] and exposure to biomass cooking fuels [31].…”
Section: Introductionmentioning
confidence: 99%